Identification of genetic determinants associated with susceptibility and therapeutic efficacy in Philadelphia-negative Myeloproliferative Neoplasms - Azevedo, Ana P. (2016)
Poster presented at the Scientific Toxomics Meeting, 28 September 2015, Lisbon, Portugal.